Productivity Effects of Privately and Publicly Funded R&D - Karin Bergman (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper examines the productivity effects of privately and publicly funded R&D, both performed in the private sector. In doing so, it ascertains whether there are differences in the direct effects on an industry's total factor productivity growth, and whether the spillover effects of R&D performed in other industries within a country differ in terms of the two sources of funding. Using a panel of industries from 13 OECD countries, it is found that privately funded R&D has a positive productivity effect, but with diminishing returns. Publicly funded R&D shows signs of increasing returns to scale, but the total effect is negative for most industries in the sample. The results concerning spillover effects are less robust, but there is some evidence of positive spillover effects from privately funded R&D, whereas spillovers from publicly funded R&D have an insignificant or a negative effect on an industry's productivity growth.
Keywords: D24; L60; O32; 330; Privately funded R&D; publicly funded R&D; productivity